Lower creatinine levels are associated with an increased risk of depression: evidence from the China Health and Retirement Longitudinal Study - Liu, Fajin; Zhong, Xiaogang; Wang, Cuiting (Frontiers in Psychiatry, 2025)
IntroductionPrevious studies have found that depressive patients tend to have low levels of creatinine; however, the extent to which creatinine levels are associated with depression has been poorly investigated. Therefore, this study aimed to explore the relationship between creatinine levels and depression.MethodsThe participants and follow-up data from the China Health and Retirement Longitudinal Study (CHARLS), as well as metabolomics data from the Metabolite Network of Depression Database (MENDA), were collected. The 10-item Center for Epidemiologic Studies Depression Scale (CESD-10) was used to assess the severity of depression. Spearman correlation analysis, spline regression, and binary logistic regression models were employed to explore the relationship between creatinine levels and depression.ResultsA total of 7,826 participants and 3,886 follow-up participants were included in the CHARLS 2011 and 2015 surveys. Of these, 37.9% (2,966/7,826) and 34.6% (13,44/3,886) of participants experienced depression in CHARLS 2011 and 2015, respectively. The creatinine level was negatively correlated with the total CESD-10 score and dimensions scores, showing an inverse dose–response relationship between creatinine levels and depression. Compared with participants with high creatinine levels, those with middle creatinine levels were associated with a higher risk of depression (OR = 1.22, 95% CI = 1.08–1.38), while participants with low creatinine levels had the highest risk of depression (OR = 1.30, 95% CI = 1.13–1.49) in the fully adjusted model. Similar results were observed in the follow-up data, and the MENDA metabolomics data validated the negative correlation between creatinine levels and the severity of depression.ConclusionLower levels of creatinine were closely associated with a higher risk of depression, and it could serve as a potential marker for identifying individuals at high risk of depression.